Automated Visual Campimeter. - Pino H., Alfonzo; Suaste Gómez, E. (Revista Mexicana de Ingenieria Biomedica, 1991)
The development of a campimeter capable of detecting the patient’s response automatically is detailed. The routines and test patterns are handled by a computer; The results are plotted on the plane and the required angle.